Examining airline employees' work-related stress and coping strategies during the global tourism crisis - Chua, Bee-Lia; Al-Ansi, Amr; Kim, Seongseop; King, Antony Fung Wong (Emerald, 2022)
Purpose: This study aims to investigate the theoretical relationships between job stressors, psychological stress and coping strategies in the context of the global travel and tourism crisis faced by the airline industry. Design/methodology/approach: An online cross-sectional survey was designed to obtain empirical data from airline employees in South Korea and Hong Kong. A total of 366 airline employees participated in the survey through convenience sampling method. Findings: The structural equation modeling findings indicated that work schedule and demand; job insecurity and financial concerns; and role conflict played a significant role in creating psychological stress, which, in turn, determined emotion-oriented coping. The influence of the identified job stressors on psychological stress was significantly different between South Korean and Hong Kong airline employees. Practical implications: The study demonstrates ways in which airline employees react to stressful work circumstances to avoid loss of resources. Furthermore, it highlights the role that psychological stress plays in influencing airline employees to direct attention to emotion-oriented coping mechanisms. Originality/value: In view of the immense impact of the COVID-19 pandemic on the global airline industry, this study expands the role of job stressors in a peculiar and unprecedented work environment in the airline industry and accentuates the varying effects job stress may have on coping strategies from the perspective of airline employees in an Asian culture.